2017
DOI: 10.1044/2017_jslhr-s-16-0371
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence That Growth in Productive Language Differentiates Childhood Stuttering Persistence and Recovery

Abstract: Purpose: Childhood stuttering is common but is often outgrown. Children whose stuttering persists experience significant life impacts, calling for a better understanding of what factors may underlie eventual recovery. In previous research, language ability has been shown to differentiate children who stutter (CWS) from children who do not stutter, yet there is an active debate in the field regarding what, if any, language measures may mark eventual recovery versus persistence. In this study, we examined whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 57 publications
0
19
0
10
Order By: Relevance
“…The factors associated with recovery include language skills: stronger language skills in girls at age 2 predicted recovery by age 7 (Kefalianos et al, 2017); steeper growth in syntactic production (mean age at assessment 57, 71, 83 months; Leech, Ratner, Brown, & Weber, 2017). However, Spencer and Weber-Fox (2014) reported no association with receptive or expressive language skills.…”
Section: Factors Associated With Recoverymentioning
confidence: 99%
“…The factors associated with recovery include language skills: stronger language skills in girls at age 2 predicted recovery by age 7 (Kefalianos et al, 2017); steeper growth in syntactic production (mean age at assessment 57, 71, 83 months; Leech, Ratner, Brown, & Weber, 2017). However, Spencer and Weber-Fox (2014) reported no association with receptive or expressive language skills.…”
Section: Factors Associated With Recoverymentioning
confidence: 99%
“…However, after 18 months both groups showed no difference in these measures, which means that both groups performed well. These results suggest that language skills during the initial visit can disentangle the recovered group from the persistent group (Leech et al, 2017). As found in Leech et al (2017), it was connective endings which predicted who will be in the recovery group.…”
Section: Discussionmentioning
confidence: 56%
“…These results suggest that language skills during the initial visit can disentangle the recovered group from the persistent group (Leech et al, 2017). As found in Leech et al (2017), it was connective endings which predicted who will be in the recovery group. However, in the aforementioned study, lexical diversity was not found as a significant indicator as was the case in our study.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations